Inflammatory cytokines may mediate the causal relationship between gut microbiota and male infertility: a bidirectional, mediating, multivariate Mendelian randomization study - Zou, Haoxi; Xu, Ningning; Xu, Huanying; Xing, Xiaoyan; Chen, Yanfen; Wu, Suzhen (Frontiers in Endocrinology, 2024)
Studies have shown that the gut microbiota is associated with male infertility (MI).However, their causal relationship and potential mediators need more evidence to prove. We aimed to investigate the causal relationship between the gut microbiome and MI and the potential mediating role of inflammatory cytokines from a genetic perspective through a Mendelian randomization approach.This study used data from genome-wide association studies of gut microbes (Mibiogen, n = 18, 340), inflammatory cytokines (NFBC1966, FYPCRS, FINRISK 1997 and 2002, n=13, 365), and male infertility (Finngen, n=120, 706) to perform two-way Mendelian randomisation (MR), mediated MR, and multivariate of male infertility (odds ratio = 0.50, 95% confidence interval = 0.35-0.71, P = 0.0001), MCP-3 increased the risk of male infertility (odds ratio = 1.28, 95% confidence interval = 1.03-1.61, P = 0.0039). Mediated MR analysis showed that HGF mediated the causal effect of Bacteroides on MI (mediated percentage 38.9%).Multivariate MR analyses suggest that HGF may be one of the pathways through which Bacteroides affects MI, with other unexplored pathways.The present study suggests a causal relationship between specific gut microbiota, inflammatory cytokines, and MI. In addition, HGF may mediate the relationship between Bacteroides and MI.